The role of the arms in achieving the 100- meter running event for students - Dr. Wael Abdullah Hussein Al-lami (Global Scientific Publishing, 2024)
The study included four chapters, as the first chapter included the introduction and the importance of the research. The study included an objective, which is to identify the role of the arms in achieving the 100-meter run for students. As for the second chapter, it included the research methodology, as the descriptive methodology was chosen to suit the nature of the study, while the research sample included second-stage students from the College of Physical Education and Sports Sciences / University of Al-Qadisiyah, with a number of (50) students from a community of (330) students. The sample was tested to run 100 meters, then the test was repeated with the arms fixed, and the real reasons behind determining the percentage of the role of the arms in running the 100-meter event were highlighted. After presenting, analyzing and discussing the results in the third chapter, a significant difference appeared between normal running and running with the arms fixed. As for the fourth chapter, it included several conclusions, including that the arms play an important role in achieving the 100-meter run. There were a set of recommendations, including the researcher recommending that trainers divide the proportions of the method on training body parts and give the arms the percentage resulting from the current study
Keywords: Arms role; 100m effectiveness; contribution rate